Influence of Risk Factors on the Well-Being of Elderly Women with Knee Osteoarthritis - Ivana Minaković; Jelena Zvekić Svorcan; Tanja Janković; Hajdana Glomazić; Mirjana Smuđa; Dejan Živanović; Jovan Javorac; Bela Kolarš (Medicina, 2023)
Background and Objectives: Knee osteoarthritis (KOA) is a widespread chronic joint disease characterized by functional limitations and pain. Functioning restrictions exert a detrimental impact on societal integration, relationships, and psychological well-being, resulting in significant emotional distress in KOA patients. The objective of this study is to examine how various risk factors impact the emotional well-being of individuals with KOA. Materials and Methods: This prospective cross-sectional study involved 154 postmenopausal women treated at the Special Hospital for Rheumatic Diseases in Novi Sad, Serbia. The experimental group comprised 97 individuals with chronic knee pain and structural knee damage (Kellgren–Lawrence (KL) scale II-IV), while the control group had 53 individuals with chronic knee pain but no structural knee damage (KL scale 0-I). The collected data consisted of sociodemographic factors, general characteristics, associated diseases, and laboratory results. Adequate anthropometric measurements were conducted, and all subjects were required to complete the SF-36 RAND questionnaire. Results: The analysis identified several variables that independently influenced emotional well-being. These included pain intensity (beta (β) 0.21; 95% CI: 0.03–0.20; p < 0.01), social functioning (beta (β) 0.47; 95% CI: 0.23–0.43; p < 0.001), physical functioning (beta (β) 0.23; 95% CI: 0.04–0.21; p < 0.01), and education level (8–12 years: beta (β) 0.25; 95% CI: 1.47–9.41; p < 0.01; >12 years: beta (β) 0.27; 95% CI: 2.51–12.67; p < 0.01). However, the multivariate model revealed that only social functioning (beta (β) 0.57; 95% CI: 0.27–0.53; p < 0.001) and education level (8–12 years: beta (β) 0.21; 95% CI: 1.10–8.260; p < 0.05; >12 years: beta (β) 0.21; 95% CI: 1.18–10.30; p < 0.05) were significantly associated with emotional well-being in KOA patients. Conclusions: The findings of this study indicate that a reduced social functioning and a lower educational attainment are linked to a poorer emotional well-being among patients with KOA.